Audit Expectation Gap in Nigeria: Stakeholders Perspective on Causes and Possible Solutions - Sule, Safiyanu; Mohamad Yusof, Nor Zalina (2022)
This study explores stakeholders’ perceptions on the causes and possible solutions to issues concerning Audit Expectation Gap (AEG) in Nigeria. In doing so, the study employs a qualitative research method and data is collected through face-to-face interviews with 12 participants among three stakeholder groups: regulatory bodies, professional bodies, and accounting practitioners. The data were analysed using a thematic analysis. The findings indicated that the causes of the gaps are linked to the knowledge gap among the users of financial statements expectations about the audit function and the roles and responsibilities of auditors. The analysis further indicated that the AEG could be reduced through audit education, enlightening the users of financial statements about the function of an audit and the roles of auditors, financial literacy program, and media awareness on the roles of auditors and through the use and adoption of ISA 700 into financial reporting practice in Nigeria. The findings might have practical implications to regulators on how the adoption of ISA 700 could be affected to improve users understanding auditors’ reporting model in Nigeria.